2010
DOI: 10.5194/bg-7-921-2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a reciprocal peat transplant between two contrasting Central European sites on C cycling and C isotope ratios

Abstract: Abstract. An 18-month reciprocal peat transplant experiment was conducted between two peatlands in the Czech Republic. Both sites were 100% Sphagnum-covered, with no vascular plants, and no hummocks and hollows. Atmospheric depositions of sulfur were up to 10 times higher at the northern site Velke jerabi jezero (VJJ), compared to the southern site Cervene blato (CB). Forty-cm deep peat cores, 10-cm in diameter, were used as transplants and controls in five replicates. Our objective was to evaluate whether CO2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For the peat transplant experiment described here, we have reported data on carbon translocations. 39 Soon after the peat monoliths were transplanted to their host site, the imported peat moisture was flushed out and replaced by advecting bogwater of the host site. Terminal C mineralization was governed by pore water rather than by solids.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…For the peat transplant experiment described here, we have reported data on carbon translocations. 39 Soon after the peat monoliths were transplanted to their host site, the imported peat moisture was flushed out and replaced by advecting bogwater of the host site. Terminal C mineralization was governed by pore water rather than by solids.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Several previous studies (Broder, Blodau, Biester, & Knorr, ; Knorr, Glaser, & Blodau, ; Novak et al, ) have reported a shift to isotopically heavier C from the living moss to the shallowest peat sections, similar to that in Figure b. This C isotope shift in waterlogged soils has been interpreted as a result of degradation of young, labile organic molecules, with preferential removal of isotopically light C in a gaseous or liquid form (cf.…”
Section: Discussionmentioning
confidence: 66%
“…Joint interpretation of peaks in δ 13 C peat values, C/N ratios, δ 18 O H2O values, and DOC concentrations in Brumiste porewater profiles must be done with caution: These peaks were not found at the same depth. We note, however, that 210 Pb dating of vertical peat profiles at mountain‐top Sphagnum ‐dominated sites in the Czech Republic, similar to Brumiste, has shown a considerable scatter in ages of peat layers, even within a single site (Novak et al, ; ; Novak, Erel, Zemanova, Bottrell, & Adamova , ; Vile, Wieder, & Novak, ).…”
Section: Discussionmentioning
confidence: 91%
“…leaf samples. This suggests possible input from low‐abundance C 3 plants unaccounted for in the sampling strategy, that 12 C is lost preferentially during decomposition, selective decomposition of C 4 plant litter, or selective preservation of naturally 13 C‐depleted components of plant litter, i.e. lipids …”
Section: Resultsmentioning
confidence: 99%